Ethnography in education - Mills, David 1969-; Morton, Missy (Research methods in education, 2013)
The title will introduce you to ethnographic 'classics', the best existing textbooks, and debates about new approaches and innovations. With extended examples of ethnographic analysis by both established scholars and research students, the authors aim to help you cultivate an 'ethnographic imagination' in your own research and writing